Eimeria: Navigating complex intestinal ecosystems. - Shengjie Weng; Erjie Tian; Meng Gao; Siyu Zhang; Guodong Yang; Bianhua Zhou (PLoS Pathogens)
Eimeria is an intracellular obligate apicomplexan parasite that parasitizes the intestinal epithelial cells of livestock and poultry, exhibiting strong host and tissue tropism. Parasite-host interactions involve complex networks and vary as the parasites develop in the host. However, understanding the underlying mechanisms remains a challenge. Acknowledging the lack of studies on Eimeria invasion mechanism, we described the possible invasion process through comparative analysis with other apicomplexan parasites and explored the fact that parasite-host interactions serve as a prerequisite for successful recognition, penetration of the intestinal mechanical barrier, and completion of the invasion. Although it is recognized that microbiota can enhance the host immune capacity to resist Eimeria invasion, changes in the microenvironment can, in turn, contribute to Eimeria invasion and may be associated with reduced immune capacity. We also discuss the immune evasion strategies of Eimeria, emphasizing that the host employs sophisticated immune regulatory mechanisms to suppress immune evasion by parasites, thereby sustaining a balanced immune response. This review aims to deepen our understanding of Eimeria-host interactions, providing a theoretical basis for the study of the pathogenicity of Eimeria and the development of novel anticoccidial drugs.